Influencing factors of the profitability and competitiveness of the Hungarian pig farming sector - Vinkler, Béláné; Tatár, Emese; Daróczi, Miklós; Gábrielné Tőzsér, Györgyi (Animal welfare, Ethology and Housing Systems (AWETH), 2014)
Pig farming has very old traditions in Hungary and it plays a key role in the domestic livestock sector. The number of pigs was more than 5 million 10 years ago, and it decreased to 3 million until June 2012. The number of pig stock in 2012 was only 47% of the number in 2004, nevertheless, a slight increase can be observed in the past few years. According to the data of Hungarian Central Statistical Office, the pig stock of the private enterprises decreased significantly in the past years. The share of pig farming in the national economy depends on the number of pigs and the income generating capacity of the sector. The private holdings (in contrast with large corporations) have low capital strength and they have serious liquidity problems, which may endanger their profitability, competitiveness and their long-term activity. In this paper, the authors wish to analyse these problems using the financial data of the pig producing enterprises in the period of 2007-2012, analyzing the financial situation, capital structure, the profitability and the efficiency of their management.
Keywords: pig farming; financial situation; competitiveness; profitability